Intervensi Konseling dalam Penanganan Anak dengan Attention Deficit Hyperactivity Disorder (ADHD) - Siti Konaah; Isabelle Clara; Aisyah Ariesca Putri; Ririn Ayu Anjar Wani; Nabilla Khairunnisa. S; Rizki Novirson (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to explore the effectiveness of various intervention strategies, including counseling services, learning strategies, and occupational therapy in treating children with Attention Deficit Hyperactivity Disorder (ADHD). Through a qualitative method based on literature studies, this study applies systematic data processing to evaluate the impact of a holistic approach on children's behavior and concentration. Analysis is carried out through data reduction procedures, data presentation, and verification of conclusions to measure the extent to which a holistic approach influences the development of children's behavior and concentration abilities. The results of the study indicate that multimodal approaches, such as Cognitive Behavior Therapy (CBT) and occupational therapy, are effective in improving children's self-control, emotional regulation, and motor skills. In addition, the implementation of an Individual Learning Program (IPP) in schools and intensive collaboration with parents play a major role in creating a supportive environment for children with ADHD. This study concludes that integrated treatment between behavioral interventions and the success of optimizing children's potential depends heavily on the integration of professional behavioral treatment with active support from the family.